Outcome comparison of mitral valve surgery and MitraClip therapy in patients with severely reduced left ventricular dysfunction. (23rd May 2020) - Gyoten, Takayuki; Schenk, Sören; Rochor, Kristin; Herwig, Volker; Harnath, Axel; Grimmig, Oliver; Just, Sören; Fritzsche, Dirk; Messroghli, Daniel
Abstract: Aims: The aim of this study was to compare the outcomes of surgical mitral valve repair or replacement (sMVR) and percutaneous edge‐to‐edge repair using MitraClip (pMVR) in patients with severe left ventricular dysfunction affected by functional mitral regurgitation (FMR). Methods and results: We retrospectively identified 132 patients with left ventricular ejection fraction (LVEF) ≦ 30% submitted to sMVR ( n  = 47) or pMVR ( n  = 85) for FMR at our centre from January 2013 to December 2017. To adjust for baseline imbalances, we used a propensity score matching by age, logistic EuroSCORE, and left ventricular end‐systolic volume. After being matched, MitraClip therapy showed lower perioperative mortality and rate of complications yet increased residual mitral regurgitation (MR) grade than did surgery (0.2 ± 0.50 in sMVR vs. 1.3 ± 0.88 in pMVR, P  < 0.0001). According to stratified multivariate Cox model analysis, residual MR severity was an independent risk factor for cardiac death [hazard ratio (HR), 2.81; 95% confidence interval [CI], 1.44–5.48, P  = 0.0025] and re‐hospitalization for heart failure (HR, 3.07; 95% CI, 1.50–6.29, P  = 0.0022) at 1 year follow‐up. Stratified multivariable Cox regression analysis at 3 years identified pMVR as risk factor for cardiac death (HR, 0.19; 95% CI, 0.040–0.86, P  = 0.031) and re‐hospitalization for heart failure (HR, 0.28; 95% CI, 0.077–0.99, P  = 0.048). Conclusions: In patients with FMR and LVEF ≤ 30%, MitraClip therapy resulted in lower perioperative complications and mortality than sMVR. However, surgically treated patients who survived the perioperative stage had less residual MR and experienced lower rates of re‐hospitalization for heart failure at 1 year and lower cardiac mortality at 1 and 3 years of follow‐up than did patients undergoing pMVR.